Decline in gait propulsion in older adults over age decades - Sloot, Lizeth H.; Malheiros, Susanne; Truijen, Steven; Saeys, Wim; Mombaur, Katja; Hallemans, Ann; van Criekinge, Tamaya (Gait & posture, 2021)
Background - Despite strong evidence that walking speed and forward propulsion decline with increasing age, their relationship is still poorly understood. While changes in the ankle and hip mechanics have been described, few studies have reported the effect of ageing on the whole leg’s contribution to propulsion. - Research question - The aim of this study was to investigate age-related changes in the work performed by the leg on the center of mass (COM) push-off power during walking in adults aged 20-86 years. Specifically, we evaluated how deterioration in COM push-off power relates to changes in ankle and hip kinetics as well as age and walking speed. - Methods - Motion, ground reaction forces and gastrocnemius muscle activity were recorded in 138 adults during overground walking at self-selected speed. Age-related differences in variables between decades were analyzed with an ANOVA, while the relation between COM push-off power and joint kinetic variables, as well as walking speed and biological age, was evaluated using correlations and multiple regression analysis. - Results - From the age of 70 years and onwards, COM push-off power was significantly decreased. The decline in COM push-off power was mostly explained by a decline in average ankle push-off power (72 %), and to a lesser extent by peak hip extension moment (3 %). There was no re-distribution of ankle-to-hip push-off power. The decline in COM push-off power seemed more related to walking speed (explaining 54 % of the variance) than biological age (only 4 %). - Significance - Findings indicate that age-related decline in COM push-off power in able-bodied adults starts from the age of 70 years, which is before changes have been found in kinematics, but still later than generally presumed. This decrease in push-off power was more related to walking speed than biological age, which emphasizes the need to better understand the reason for speed decline in older adults.